Vpliv štartne številke in smuči izbranega proizvajalca na rezultate vrhunskih tekmovalcev v alpskem smučanju - Lešnik, Blaž (Šport (Ljubljana), 2013)
Using a sample of 107 elite Alpine skiers, we aimed to establish whether there was any relationship between: 1) a competitor's start number and the times they achieved in individual course sections; and 2) the times achieved in individual course sections and the manufacturer of the skis used in Slalom competitions at the Europa Cup. The slalom course was divided into eight sections; the times achieved in each section and in the entire course were measured separately with a kinematic analysis and the relative lags of the competitors were calculated. The start number and the most commonly used ski manufacturer (Fischer) contributed 53.2% of the explained variance to the overall time. We also proved that the partial effect of the start number on the time achievement in all eight sections was statistically significant, whereas the effect of the ski manufacturer Fischer on the achieved times in eight sections of the course was statistically significant only in the last section (PT/8). In Alpine skiing competitions the times in the course sections and the final time are strongly influenced by the start number, whereas a similar influence of the skis on the partial or final result was not confirmed.
Keywords: alpsko smučanje; čas; European Cup; evropski pokal; kinematics; kinematika; proizvajalci smuči; ski manufacturers; slalom; starting number; štartna številka; time